2009
DOI: 10.1186/2047-783x-14-5-206
|View full text |Cite
|
Sign up to set email alerts
|

Biliary diseases in heart transplanted patients: a comparison between cyclosporine a versus tacrolimus-based immunosuppression

Abstract: A cyclosporine (CsA)-based immunosuppression is associated with an increased incidence of cholelithiasis after heart transplantation. It is not known if tacrolimus (Tac) has comparable biliary side effects in humans.We evaluated the incidence of gallbladder sludge and cholelithiasis under Tac-based immunosuppression by ultrasound examinations in 31 cardiac transplants (25 male, 6 female, mean age: 59 ± 11 years). Data were compared to 57 patients (47 male, 10 female, mean age: 58 ± 11 years) who received CsA-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…(1,2) The choice of immunosuppressive program directly affects the transplant effect. The main reason is that immunosuppressant produces toxic side effects on multiple organs of the body after transplanting.…”
Section: Introductionmentioning
confidence: 99%
“…(1,2) The choice of immunosuppressive program directly affects the transplant effect. The main reason is that immunosuppressant produces toxic side effects on multiple organs of the body after transplanting.…”
Section: Introductionmentioning
confidence: 99%
“…For example octreotide, a somatostatin analogue, has been implicated in gallstone formation via reduced intestinal transit, hence precipitating lithogenic bile salt pool formation by intestinal bacteria [94,95]. Calcineurin inhibitors, namely ciclosporin and tacrolimus, are also reported to cause gallstones by inhibiting the hepatocanalicular bile salt export pump [96,97]. A class of cholesterol-lowering drugs, known as fibrates, may increase the risk of gallstones as a result of increased biliary cholesterol saturation and reduced bile salt synthesis [98].…”
Section: Environmental Factorsmentioning
confidence: 99%
“…In addition to TPN, prior studies have suggested that the use of calcineurin inhibitors is associated with increased rates of gallstones and acute cholecystitis, although this has not been studied specifically in the HSCT population [26,27]. It is possible that the routine administration of calcineurin inhibitors may have contributed to the high rate of cholecystitis observed in our cohort.…”
Section: Discussionmentioning
confidence: 85%